2009
DOI: 10.4049/jimmunol.0902811
|View full text |Cite
|
Sign up to set email alerts
|

Immune Gene and Cell Enrichment Is Associated with a Good Prognosis in Ependymoma

Abstract: Approximately 50% of children with ependymoma will suffer from tumor recurrences that will ultimately lead to death. Development of more effective therapies and patient stratification in ependymoma mandates better prognostication. In this study, tumor gene expression microarray profiles from pediatric ependymoma clinical samples were subject to ontological analyses to identify outcome-associated biological factors. Histology was subsequently used to evaluate the results of ontological analyses. Ontology analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 52 publications
2
55
1
Order By: Relevance
“…RAB12 is a Ras oncogene family member and is overexpressed in colorectal cancers (44). Furthermore, the COLEC12 gene is known prognostic marker in anaplastic thyroid cancer and brain tumors (45,46). Because of limited clinical annotation of the TCGA data, we were unable to validate these as prognostic markers in the TCGA cohort.…”
Section: Discussionmentioning
confidence: 84%
“…RAB12 is a Ras oncogene family member and is overexpressed in colorectal cancers (44). Furthermore, the COLEC12 gene is known prognostic marker in anaplastic thyroid cancer and brain tumors (45,46). Because of limited clinical annotation of the TCGA data, we were unable to validate these as prognostic markers in the TCGA cohort.…”
Section: Discussionmentioning
confidence: 84%
“…Apart from histological grade and incomplete resection, several prognostic markers have been studied in ependymomas including Ki-67 [3], survivin [1], human telomerase reverse transcriptase, ERBB family members [11] and nucleolin [30]. Whole genome approaches such as array comparative genomic hybridization [20; 24; 28] and gene expression profiling [8; 16; 25; 27; 34] have also been employed for the identification of prognostic biomarkers. However, despite these studies molecular markers for disease prognosis have not been integrated into the clinical management of ependymomas.…”
Section: Introductionmentioning
confidence: 99%
“…Often revealed by hierarchical clustering techniques or outcome correlation studies, these signatures distinguish multiple different immune cell types [32][33][34][35][36][37] and recapitulate immunohistochemistry-based observations in breast cancer that link tumor-infiltrating immune cell abundance to disease-free survival and overall survival of patients [30,[36][37][38][39][40][41][42]. More recently, similar studies involving presurgical breast tumor biopsies have begun to demonstrate associations between immunity-related genes and tumor responsiveness to neoadjuvant chemotherapy [22,44,45,63,64].…”
Section: Discussionmentioning
confidence: 74%
“…Indeed, the mere abundance of tumor-infiltrating leukocytes, namely CD3+/CD8+ T lymphocytes, has been robustly correlated with pCR in the neoadjuvant setting [22][23][24][25] as well as relapse-free and overall survival of breast cancer patients [25][26][27][28][29]. In more recent years, microarray expression profiling studies in breast and other tumor types have identified immune gene signatures from whole tumor RNA extracts that reflect the abundance of tumor-infiltrating immune cells [30][31][32][33][34][35][36][37][38]. We and others have found that the biological and phenotypic properties of the genes comprising these signatures implicate distinct immune cell lineages [34][35][36][37]39,40], and that combinations of these immune genes correlate with patient outcomes ranging from recurrence-free survival [30,32,[36][37][38][39][40][41][42][43] to tumor regression in the neoadjuvant setting [44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%